Adsorption and Squeeze Performance of PAMAM-PGlu Inhibitors for Silicate Scale Mitigation Due to ASP Flooding - Bee Chea Tan; Ismail Mohd Saaid; Siti Qurratu’ Aini Mahat; Suzalina Zainal; Astriyana Anuar; Petrus Tri Bhaskoro (Platform, a Journal of Engineering)
Silica and silicate scale deposition in the production systems resulted in reduced production rates and equipment damages. Chemical scale inhibition using squeeze method is advantageous for petroleum reservoir conditions. This paper aims to assess the adsorption and squeeze performance of developed scale inhibitors that consist of polyamidoamine (PAMAM) dendrimers and pteroyl-L-glutamic acid (PGLU). Commercial inhibitor, diethylenetriamine penta(methylene phosphonic acid), also known as DETPMP, was also used to benchmark the laboratory findings. Static adsorption test and core flooding were performed to investigate the adsorption characteristics and retention of the inhibitors in Berea sandstone cores. Simulation was also conducted to estimate the squeeze performance of the inhibitors. Results revealed that PAMAM-2-PGLU scale inhibitor exhibited the highest adsorption and retention in the sandstone core. The treatment of PAMAM-2-PGLU and PAMAM-1-PGLU inhibitors increased the core permeabilities. SQUEEZE IV model predicted that both PAMAM-PGLU inhibitors yielded longer squeeze lifetime than DETPMP inhibitor. Both experimental and simulation results showed good fit in terms of adsorption and squeeze lifetime. In this paper, the tested PAMAM-PGLU scale inhibitors have demonstrated better adsorption, retention, and squeeze lifetime in sandstone formation. They could offer effective and low-toxicity alternatives to commercial inhibitors due to raising environmental concerns.